Prognostic impact of shock at ICU admission in acute respiratory failure - Tae Wan Kim; Jae Young Choi; Joonho Lee; Jin Song Park; Chi Ryang Chung; Jeong Hoon Yang; Gee Young Suh; Ryoung-Eun Ko (PLoS ONE, 2026)
Background Acute respiratory failure (ARF) is a leading cause of intensive care unit (ICU) admission and is frequently complicated by shock. However, the prognostic significance of shock at ICU admission across the heterogeneous ARF population remains incompletely defined. We aimed to evaluate the association between shock at ICU admission and mortality in patients with ARF. Methods This retrospective cohort study included 3,497 adult patients with ARF admitted to a tertiary medical center ICU in South Korea between January 2019 and December 2023. Shock was defined as the need for vasopressor or inotropic support at ICU admission. The primary outcome was hospital mortality, and the secondary outcome was ICU mortality. Multivariable Cox proportional hazards models were used to estimate adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs). Results Among 3,497 patients, 652 (18.6%) had shock at ICU admission. Patients with shock had significantly higher ICU mortality (46.4% vs. 17.1%) and hospital mortality (56.4% vs. 26.2%) compared with those without shock. After adjustment for potential confounders, shock remained independently associated with increased ICU mortality (aHR 1.84; 95% CI 1.56–2.17) and hospital mortality (aHR 1.58; 95% CI 1.37–1.82). This association was consistent across subgroups stratified by illness severity, respiratory support modality, and neutropenia status. Conclusion Shock at ICU admission was independently associated with increased mortality in patients with ARF, with consistent findings across clinically relevant subgroups. The presence of shock at ICU admission may serve as a readily identifiable marker for risk stratification in this population.